Graphene-loaded iron-coated cobalt-nickel alloy nanoparticles and preparation method thereof
Through the preparation method of graphene-supported iron-clad cobalt-nickel alloy nanoparticles, the problem of insufficient stability and performance of iron-cobalt-nickel nanomaterials in hydrogen production catalysts is solved, and a catalytic material with high stability and high performance is achieved.
Patent Information
- Application Number
- CN202411839272.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-07
AI Technical Summary
The existing iron-cobalt nickel nanomaterials have insufficient stability and performance when producing hydrogen catalysts, resulting in low use potential.
The preparation method of graphene-supported iron-covered cobalt-nickel alloy nanoparticles is adopted. By atomizing and drying the cobalt-nickel alloy nanoparticles with iron salt and graphene oxide, graphene is formed by forming graphene-supported iron-covered cobalt-nickel alloy nanoparticles, and an iron atom layer and graphene are formed through a calcination reduction step.
The high stability and high specific surface area of graphene-supported iron-clad cobalt-nickel alloy nanoparticles are achieved, the performance of catalytic materials is improved, and the technical gap in this field is filled.
Smart Images

Figure CN119566295A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy nano material preparation, and in particular relates to graphene-supported iron-coated cobalt-nickel alloy nanoparticles, and also relates to a preparation method of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles. Background Art
[0002] Iron-coated cobalt-nickel alloy nanomaterials have excellent physical and chemical properties due to their nanoparticle characteristics such as surface and interface effects, small size effects, quantum size effects and macroscopic quantum tunneling effects. Among them, using cobalt-nickel alloy particles as the substrate and uniformly coating a layer of iron atoms on their surface can greatly improve the utilization rate of iron elements and the stability of the material structure. In addition, the introduction of carrier graphene can also greatly improve the conductivity of the material.
[0003] At present, the preparation of graphene-supported iron-coated cobalt-nickel alloy nanoparticles has not been reported, but there are many studies on the preparation of iron-cobalt-nickel ternary nanomaterials, and the main preparation methods are: powder metallurgy, hydrothermal synthesis and electrochemical deposition. The prepared iron-cobalt-nickel alloy nanoparticles are mainly used as catalysts for hydrogen production by electrolysis of water, but iron-cobalt-nickel nanomaterials often have insufficient stability and performance in hydrogen production catalysts, resulting in low potential for use.
[0004] The patent with publication number CN115976592A discloses a device for producing hydrogen by electrolysis of water using iron-cobalt-nickel nanomaterials and its preparation method and application. The method is synthesized by dissolving an iron source, a cobalt source and a nickel source in a solvent to obtain a precursor solution, immersing nickel foam in the precursor solution, and electrochemically depositing the nickel foam to obtain the iron-cobalt-nickel nanomaterial. The iron-cobalt-nickel nanomaterial can be used as an electrode material to perform hydrogen and oxygen evolution and full hydrolysis reactions in an alkaline environment. Since the method does not use precious metals such as platinum and ruthenium, and does not require long-term hydrothermal or high-temperature calcination, the preparation process is simple and fast, and the cost is low. However, the method is not suitable for preparing iron-clad cobalt-nickel alloy nanoparticles, and the prepared iron-cobalt-nickel nanomaterial has general performance and poor stability in the electrolysis of water catalysis process, so it has little reference value.
[0005] The patent with publication number CN201911375469.2 discloses an iron-cobalt-nickel-copper-based high entropy alloy electrolytic water catalytic material and its preparation method. The electrolytic water catalytic material is composed of a reactive substance and a carrier, and the reactive substance is an iron-cobalt-nickel-copper-tin, iron-cobalt-nickel-copper-manganese, iron-cobalt-nickel-copper-vanadium and other iron-cobalt-nickel-copper-based high entropy alloy nanoparticles, and the carrier is a carbon nanofiber material prepared by electrostatic spinning. The electrolytic water catalytic material prepared by the present invention has a high specific surface area, is conducive to the diffusion of the electrolyte and the desorption of the gas, can produce hydrogen and oxygen under alkaline conditions, and the hydrogen production rate under high voltage is much higher than 20% Pt / C electrode. At the same time, carbon nanofibers can effectively protect high entropy alloy nanoparticles from the erosion of the electrolyte, and give the catalytic material good stability. However, the preparation method is complicated, the output is very small, and it is only suitable for small-batch preparation in the laboratory, and the method is not suitable for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles. Summary of the invention
[0006] The first object of the present invention is to provide a method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles.
[0007] The second purpose of the present invention is to provide graphene-supported iron-coated cobalt-nickel alloy nanoparticles, which solve the technical problems of insufficient stability and performance of iron-cobalt-nickel nanomaterials when used as hydrogen production catalysts.
[0008] The first technical solution adopted by the present invention is a method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles, comprising the following steps: S1: Mix cobalt and nickel salts to prepare a precursor mixed solution, add ascorbic acid to the precursor solution, stir, and react at room temperature for half an hour to obtain a cobalt-nickel alloy nanoparticle suspension; S2: adding an appropriate amount of iron salt and graphene oxide to the cobalt-nickel alloy nanoparticle suspension, stirring evenly and then atomizing and drying to obtain a precursor powder; S3: calcining and reducing the precursor powder obtained in S2 to obtain graphene-supported iron-coated cobalt-nickel alloy nanoparticles.
[0009] The first technical solution of the present invention is also characterized in that: The atomic ratio of cobalt and nickel in S1 is 1:1, and the concentration of the precursor mixed solution is 5wt%-10wt%.
[0010] The amount of ascorbic acid added in S1 is 2-3 times the total mass of metal.
[0011] The amount of iron salt added in S2 is added according to an equal metal molar ratio.
[0012] In S2, graphene oxide is added at 2-3 times the total mass of the metal.
[0013] The atomization temperature in S2 is 150°C-180°C.
[0014] In S3, the calcination temperature is 400°C-600°C, and the calcination time is 0.5h~2h.
[0015] The second technical solution adopted by the present invention is that graphene-supported iron-coated cobalt-nickel alloy nanoparticles are prepared by the above-mentioned method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles. The particle size distribution of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles is 10nm-50nm, and the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the thickness of the iron element layer is less than 10nm.
[0016] The beneficial effects of the present invention are: The invention prepares cobalt-nickel alloy nanoparticles first, then adds iron salt and graphene oxide and performs atomization drying treatment, so that the iron salt is uniformly coated on the surface of the cobalt-nickel alloy and loaded on the surface of the graphene oxide, and finally reduces the iron ions on the surface of the cobalt-nickel alloy through calcination reduction, forms an iron atom layer on the surface of the cobalt-nickel alloy, and the graphene oxide is reduced to graphene, and the iron-coated cobalt-nickel alloy particles and the graphene surface form chemical bonds and are firmly anchored on the graphene surface; therefore, the obtained graphene-supported iron-coated cobalt-nickel alloy nanoparticles have very high stability, high specific surface area, and more surface metal atoms are exposed, have excellent application potential in the field of catalytic materials, and fill the current preparation technology gap for graphene-supported iron-coated cobalt-nickel alloy nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 TEM image of graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in Example 2 of the present invention; Figure 2 This is the element surface distribution diagram of graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] Example 1 The preparation method of graphene-supported iron-coated cobalt-nickel alloy nanoparticles disclosed in the present invention comprises the following steps: S1: a precursor mixed solution with a concentration of 5wt%-10wt% is prepared by mixing cobalt and nickel salts in an atomic ratio of 1:1, and ascorbic acid 2-3 times the total mass of the metal is added to the precursor solution, stirred, and reacted at room temperature for half an hour to obtain a cobalt-nickel alloy nanoparticle suspension; S2: Add iron salt in an equal metal molar ratio, add graphene oxide in an amount of 2-3 times the total mass of the metal, add the iron salt and graphene oxide to the cobalt-nickel alloy nanoparticle suspension, stir evenly and then atomize and dry at 150°C-180°C to obtain a precursor powder; wherein, through the atomization drying technology, the iron ions can be effectively and evenly coated on the surface of the cobalt-nickel alloy, providing a guarantee for the subsequent calcination reduction.
[0020] S3: calcining the precursor powder obtained in S2 at 400° C.-600° C. for 0.5 h-2 h for reduction to obtain graphene-supported iron-coated cobalt-nickel alloy nanoparticles.
[0021] The invention first prepares cobalt-nickel alloy nanomaterials, and by controlling the preparation parameters, the particle size of cobalt-nickel alloy nanoparticles can be effectively controlled to prepare for the subsequent coating of metallic iron. At the same time, the prepared cobalt-nickel alloy nanoparticles have a stable structure to ensure the stability of the iron-coated cobalt-nickel alloy nanostructure. The preparation method of the invention is simple, easy to implement, green and environmentally friendly, and suitable for industrial production.
[0022] The graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared according to Example 1 have a particle size distribution of 10nm-50nm, and the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the iron element layer thickness is less than 10nm. The graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared by the present invention have a stable structure, and the iron atoms evenly form an atomic layer on the surface of the cobalt-nickel alloy, and the graphene oxide is reduced to graphene, and the iron-coated cobalt-nickel alloy particles and the graphene surface form a chemical bond, which is firmly anchored on the graphene surface, thereby improving the stability of the catalyst. As a highly conductive material, graphene also ensures catalytic performance.
[0023] Example 2 This embodiment includes the following steps: S1: The atomic ratio of cobalt and nickel is 1:1, dissolved in deionized water, the solution concentration is 5wt% (total metal content), the amount of ascorbic acid added is twice the total mass of the metal, stirred, reacted at room temperature for half an hour, and a cobalt-nickel alloy nanoparticle suspension was obtained.
[0024] S2: Add an equimolar amount of iron salt to the cobalt-nickel alloy nanoparticle suspension, stir evenly, add 2 times the amount of metal oxide after dissolution, stir evenly, and atomize and dry at an atomization temperature of 150°C to obtain an iron-coated cobalt-nickel precursor powder.
[0025] S3: placing the iron-coated cobalt-nickel precursor powder in a tubular furnace, calcining and reducing it, the calcination temperature is 400°C, and the insulation time is 0.5h, and finally obtaining graphene-supported iron-coated cobalt-nickel alloy nanoparticles. After testing, the particle size distribution of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment is 10nm-50nm, the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the thickness of the iron element layer is less than 10nm.
[0026] Figure 1 TEM image of graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment. Figure 1 It can be seen that the nanoparticles are evenly distributed on the graphene surface.
[0027] Figure 2 The element distribution diagram of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment is shown in FIG. Figure 2 It can be seen that the nickel and cobalt elements are evenly dispersed in the interior, and the iron element is evenly distributed in the outer layer.
[0028] The graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared by the present invention have been shown to exhibit excellent performance in anode oxygen evolution in water electrolysis to produce hydrogen under alkaline conditions. The performance is far superior to that of iron-cobalt-nickel nanomaterials reported in the literature, and has a lower catalytic potential, as shown in Table 1.
[0029] Table 1
[0030] Example 3 This embodiment includes the following steps: S1: The atomic ratio of cobalt and nickel is 1:1, dissolved in deionized water, the solution concentration is 7.5wt% (total metal content), the amount of ascorbic acid added is 2.5 times the total mass of the metal, stirred, reacted at room temperature for half an hour, and a cobalt-nickel alloy nanoparticle suspension was obtained.
[0031] S2: Add an equimolar amount of iron salt to the cobalt-nickel alloy nanoparticle suspension, stir evenly, add 2.5 times the amount of metal oxide graphite after dissolution, stir evenly, and atomize and dry at an atomization temperature of 165°C to obtain an iron-coated cobalt-nickel precursor powder.
[0032] S3: placing the iron-coated cobalt-nickel precursor powder in a tubular furnace, calcining and reducing it at a calcination temperature of 500° C. for a holding time of 1.25 h, and finally obtaining graphene-supported iron-coated cobalt-nickel alloy nanoparticles.
[0033] After testing, the particle size of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment is distributed in the range of 30nm-50nm, the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the thickness of the iron element layer is less than 10nm.
[0034] Example 4 This embodiment includes the following steps: S1: The atomic ratio of cobalt and nickel is 1:1, dissolved in deionized water, the solution concentration is 10wt% (total metal content), the amount of ascorbic acid added is 3 times the total mass of the metal, stirred, reacted at room temperature for half an hour, and a cobalt-nickel alloy nanoparticle suspension was obtained.
[0035] S2: Add an equimolar amount of iron salt to the cobalt-nickel alloy nanoparticle suspension, stir evenly, add 3 times the amount of metal oxide after dissolution, stir evenly, and atomize and dry at an atomization temperature of 180°C to obtain an iron-coated cobalt-nickel precursor powder.
[0036] S3: placing the iron-coated cobalt-nickel precursor powder in a tubular furnace, calcining and reducing it, the calcination temperature is 600°C, and the insulation time is 2h, and finally obtaining graphene-supported iron-coated cobalt-nickel alloy nanoparticles. After testing, the graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment have a particle size distribution of 20-50nm, the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the iron element layer thickness is less than 10nm.
[0037] Example 5 This embodiment includes the following steps: S1: The atomic ratio of cobalt and nickel is 1:1, dissolved in deionized water, the solution concentration is 5wt% (total metal content), the amount of ascorbic acid added is 3 times the total mass of the metal, stirred, reacted at room temperature for half an hour, and a cobalt-nickel alloy nanoparticle suspension was obtained.
[0038] S2: Add an equimolar amount of iron salt to the cobalt-nickel alloy nanoparticle suspension, stir evenly, add 3 times the amount of metal oxide after dissolution, stir evenly, and atomize and dry at an atomization temperature of 150°C to obtain an iron-coated cobalt-nickel precursor powder.
[0039] S3: placing the iron-coated cobalt-nickel precursor powder in a tubular furnace, calcining and reducing it, the calcination temperature is 600°C, and the insulation time is 0.5h, and finally obtaining graphene-supported iron-coated cobalt-nickel alloy nanoparticles. After testing, the particle size distribution of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment is 30nm-50nm, the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the iron element layer thickness is less than 10nm.
[0040] Example 6 This embodiment includes the following steps: S1: The atomic ratio of cobalt and nickel is 1:1, dissolved in deionized water, the solution concentration is 10wt% (total metal content), the amount of ascorbic acid added is 3 times the total mass of the metal, stirred, reacted at room temperature for half an hour, and a cobalt-nickel alloy nanoparticle suspension was obtained.
[0041] S2: Add an equimolar amount of iron salt to the cobalt-nickel alloy nanoparticle suspension, stir evenly, add 3 times the amount of metal oxide after dissolution, stir evenly, and atomize and dry at an atomization temperature of 150°C to obtain an iron-coated cobalt-nickel precursor powder.
[0042] S3: placing the iron-coated cobalt-nickel precursor powder in a tubular furnace, calcining and reducing it, the calcination temperature is 600°C, and the insulation time is 2h, and finally obtaining graphene-supported iron-coated cobalt-nickel alloy nanoparticles. After testing, the particle size distribution of the graphene-supported iron-coated cobalt-nickel alloy nanoparticles prepared in this embodiment is 40nm-60nm, the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the thickness of the iron element layer is less than 10nm.
[0043] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0044] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0045] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles, characterized in that: The following steps are involved: S1: Mix cobalt and nickel salts to prepare a precursor mixed solution, add ascorbic acid to the precursor solution, stir, and react at room temperature for half an hour to obtain a cobalt-nickel alloy nanoparticle suspension; S2: adding an appropriate amount of iron salt and graphene oxide to the cobalt-nickel alloy nanoparticle suspension, stirring evenly and then atomizing and drying to obtain a precursor powder; S3: calcining and reducing the precursor powder obtained in S2 to obtain graphene-supported iron-coated cobalt-nickel alloy nanoparticles.
2. The method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles according to claim 1, characterized in that: The atomic ratio of cobalt to nickel in the S1 is 1:1, and the concentration of the precursor mixed solution is 5wt%-10wt%.
3. The method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles according to claim 2, characterized in that: The amount of ascorbic acid added in S1 is 2-3 times the total mass of the metal.
4. The method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles according to claim 1, characterized in that: The amount of iron salt added in S2 is added according to an equal metal molar ratio.
5. The method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles according to claim 4, characterized in that: The graphene oxide in S2 is added at 2-3 times the total mass of the metal.
6. The method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles according to any one of claims 4 or 5, characterized in that: The atomization temperature in S2 is 150°C-180°C.
7. The method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles according to claim 1, characterized in that: In the S3, the calcination temperature is 400°C-600°C, and the calcination time is 0.5h-2h.
8. Graphene-supported iron-coated cobalt-nickel alloy nanoparticles, using the method for preparing graphene-supported iron-coated cobalt-nickel alloy nanoparticles as described in any one of claims 1 to 7, characterized in that: The particle size distribution of graphene-supported iron-coated cobalt-nickel alloy nanoparticles is 10nm-50nm, the iron element is evenly distributed on the surface of the cobalt-nickel alloy, and the thickness of the iron element layer is less than 10nm.
Citation Information
Patent Citations
Iron-cobalt-nickel-copper-based high-entropy alloy water electrolysis catalytic material and preparation method thereof
CN111185188A
Iron-cobalt-nickel nano material, water electrolysis hydrogen production device and preparation method and application of iron-cobalt-nickel nano material
CN115976592A